The Performing Arts in Ancient Java: Historical and Archaeological Studies - Soni Sadono; Pandanwangi, Brilindra (BRIN, 2025)
This research was conducted to investigatesthe development of performing arts through historical and archaeological evidence, including inscriptions, temple reliefs, literary texts, and performing arts artifacts. This research aims to explore the cultural significance of the performing arts in ancient Java and how the influence of Hindu-Buddhist culture transformed traditional art forms into more structured and complex ones. This focus emerges from the limited understanding of how performing arts shaped and reinforced social solidarity in Javanese society. This research employs historical methodology with a qualitative descriptive approach. This method includes four main stages: (1) Heuristics collection data from written sources (inscriptions, kakawin, and historical texts) and unwritten sources (artifacts and temple reliefs); (2) Criticism to evaluate the authenticity and credibility of sources through external and internal criticism; (3) Interpretation to analyze the meaning and relationship between historical data; and (4) Historiography to compile a coherent historical story. The results show that the performing arts in ancient Java, such as wayang and gamelan, developed rapidly through the adaptation of Hindu-Buddhist values. Wayang, which was originally a medium for ancestral worship, transformed into a means of entertainment and a medium for delivering Indian epics such as the Mahabharata and Ramayana. Reliefs on temples such as Borobudur and Prambanan illustrate the integral role of dance and music as an important part of the social and religious life of ancient Javanese society. In addition, the art of comedy has also developed as entertainment that conveys moral messages and enlivens the social atmosphere.